المخالفات والجنح المتعلقة بقانون المرور - سليم ﷴ -سالمي حسين (جامعة المسيلة, 2020)
ResumeMarriage contract has several implications, and the most prominent of which are rights and duties between the spouses during their life. So, There are rights and duties for the husband over his wife and likewise for the wife over her husband, there are also common rights and duties between the spouses, organized by Islamic law according to organized and framed principles. These rights and duties are obligated by Islamic Sharia for both The spouses, that they cannot be abandoned or violated , in order to live in a family of stability, affection and mercy.between the spouses the Algerian legislator tackled these rights and duties through the Algerian law of family through the last amendment 02/05, within legal articles through which it addressed the most prominent rights and duties, and in case of the absence of a legal text, the judge refers to the rules of the Islamic Sharia, Article (222) of the Algerian Code of Family
Keywords: عقد الزواج -الحقوق -الواجبات